(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The purpose of the interdiction and curatorship is to look after the interests of the person who, due to his personal condition, does not have the possibility of managing his or her own business acts, since the factual assumption of the prohibition is his or her own disability. It is the curator’s task to provide the best for the interdict, assuming the state commitment, bearing with munus publicum of which he must give an annual account. It is true that the annual reporting in practice is only done when the Public Prosecutor’s Office so requires in the injunction documents, in contrast to the legislation that determines the presentation of the annual reporting. The objective of this study is to highlight the need for external control practiced by the Public Prosecutor’s Office, requiring expressly in all processes that is decreed prohibition of person who receives income or owns property, to the presentation of annual balance sheet. For this, a research by deductive method from literature review was